Animal Models for Human-Pathogenic Coronavirus and Animal Coronavirus Research - Fenglian Xiao; Jincheng Hu; Minsheng Xu; Di Wang; Xiaoyan Shen; Hua Zhang; Jie Miao; Haodong Cai; Jihui Wang; Yaqing Liu; Shan Xiao; Longchao Zhu (Viruses)
Coronavirus epidemics have posed a serious threat to both human and animal health. To combat emerging infectious diseases caused by coronaviruses, various animal infection models have been developed and applied in research, including non-human primate models, ferret models, hamster models, mouse models, and others. Moreover, new approaches have been utilized to develop animal models that are more susceptible to infection. These approaches include using viral delivery methods to induce the expression of viral receptors in mouse tissues and employing gene-editing techniques to create genetically modified mice. This has led to the successful establishment of infection models for multiple coronaviruses, significantly advancing related research. In contrast, livestock and pets that can be infected by animal coronaviruses provide valuable insights when used as infection models, enabling the collection of accurate clinical data through the analysis of post-infection pathological features. However, despite the potential insights, there is a paucity of research data pertaining to these infection models. In this review, we provide a detailed overview of recent progress in the development of animal models for coronaviruses that cause diseases in both humans and animals and suggest ways in which animal models can be adapted to further enhance their value in research.